2018
DOI: 10.1021/acs.est.8b05253
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Potential by PM2.5 in the North China Plain: Generation of Hydroxyl Radical

Abstract: Adverse health effects of ambient PM 2.5 (d p < 2.5 μm) can be associated with the production of reactive oxygen species (ROS), among which hydroxyl radical (•OH) is the most reactive. However, •OH generated by PM 2.5 has not been quantified and studied in the North China Plain (NCP), which has suffered from heavy air pollution in recent years. In this study, PM 2.5 samples were collected at an urban site (Beijing) and a suburban site (Wangdu), extracted in a cell-free surrogate lung fluid (SLF), and •OH gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 78 publications
4
22
2
Order By: Relevance
“…1(b)), indicating that less ROS may be produced as the OC concentration increases. This is consistent with the observed relationship between typical health endpoints (e.g., ischemic heart disease, stroke, and chronic obstructive pulmonary disease) and PM exposure in epidemiological studies, 42 suggesting that OP v is an ideal indicator of adverse health effect.…”
Section: Op Of Eomsupporting
confidence: 88%
See 3 more Smart Citations
“…1(b)), indicating that less ROS may be produced as the OC concentration increases. This is consistent with the observed relationship between typical health endpoints (e.g., ischemic heart disease, stroke, and chronic obstructive pulmonary disease) and PM exposure in epidemiological studies, 42 suggesting that OP v is an ideal indicator of adverse health effect.…”
Section: Op Of Eomsupporting
confidence: 88%
“…Similar trends were observed in Seoul 43 and Beijing. 42 Studies on the contribution of chemical species to the OP of PM have identified quinones and transition metals as the main contributors. 44 The contribution of metal ions to OP could be neglected in this study, since the extraction solvents were HPLC grade (purity > 99.9%), which could mostly eliminate interference from metal ions prior to DTT assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies also found high correlations between the organic species of PM 2.5 , especially water-soluble organic carbon (WSOC), with its oxidative potential. Nevertheless, few of them have clarified the specific chemical species that were dominant in the ROS production ( Chen et al, 2019 ; Li et al, 2019c ). Ma et al (2018) have identified the individual species of water-soluble HULIS associated with the oxidative potential of PM 2.5 and found a series of aromatic acids (CHO) and nitrophenol analogs (CHON).…”
Section: Resultsmentioning
confidence: 99%